“PERINGATAN DARURAT” AS A CANCEL CULTURE MOVEMENT THROUGH SOCIAL MEDIA IN INDONESIA - Jefri Audi Wempi; Chrisdina Chrisdina; Rully Rully (Nyimak: Journal of Communication)
At that time, the Indonesian government was organizing regional elections, part of the ongoing general election process following the presidential and legislative elections. In a short period, a public movement emerged to reject and cancel the Draft Law (RUU) proposed by the Indonesian Parliament, following the Constitutional Court's ruling on presidential nomination thresholds and political party participation in elections. The "Cancel Culture" movement, known as the "Emergency Alert," quickly gained momentum and was carried out by various groups across Indonesia. It culminated in massive demonstrations involving diverse communities. This study’s key question is how the "Emergency Alert" movement, through social media, managed to oppose the regional election bill so quickly and effectively, motivating people to participate in both online and physical protests. The research aims to understand the content and platforms used in social media to shape public participation, and how the characteristics of new media triggered rapid and widespread engagement. Using new media, social media, and cancel culture theories, this qualitative research with a constructivist framework found that new media characteristics—interactivity, friendliness, richness, autonomy, playfulness, privacy, and personalization—were crucial in mobilizing support for the "Emergency Alert" movement.